2019
DOI: 10.1097/mat.0000000000001062
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin Experience in a Heterogeneous Ventricular Assist Device Population

Abstract: Ventricular assist devices (VADs) are an increasingly common therapy for end-stage heart failure across all ages as a bridge to recovery or transplant and more recently as destination therapy. With increasing experience and difficulties with establishing therapeutic heparin levels, we have begun to explore the effectiveness of direct thrombin inhibitors in this patient population. This is a retrospective review of all long-term VAD patients, both adult and pediatric, who were anticoagulated with bivalirudin be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…In the nine adult patients examined, ten bivalirudin treatment courses were recorded. The average infusion rates required to maintain anticoagulation targets were not reported [25].…”
Section: Dosing Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the nine adult patients examined, ten bivalirudin treatment courses were recorded. The average infusion rates required to maintain anticoagulation targets were not reported [25].…”
Section: Dosing Strategiesmentioning
confidence: 99%
“…Overall, aPTT values ranged from 52 to 140 s during the course of bivalirudin infusions. As a result, the authors concluded that a bivalirudin infusion initiated at a dose of 0.3 mg/kg/h and titrated to maintain a designated anticoagulation target is a reasonable dosing strategy in the setting of several differing indications [25].…”
Section: Dosing Strategiesmentioning
confidence: 99%
See 3 more Smart Citations